2007
DOI: 10.1086/519424
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Klebsiella pneumoniae Syndrome in North America

Abstract: Invasive liver abscess syndrome, which is caused by hypervirulent Klebsiella pneumoniae subtypes, has been emerging worldwide over the past 2 decades. The syndrome is associated with the hypermucoviscosity phenotype of K. pneumoniae strains and with the magA and rmpA genes. We provide the first laboratory evidence of the presence of rmpA-positive K. pneumoniae in North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
110
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 28 publications
2
110
0
2
Order By: Relevance
“…[1][2][3][4] Its emergence in western countries has also been reported. [5][6][7] Previous studies in Taiwan, Singapore and Korea found a high prevalence of the capsular polysaccharide (CPS) K antigen serotypes K1 (54.5-63.4%) and K2 (5-21.2%) of K. pneumoniae in liver abscess isolates. 1,[8][9][10] Apart from the capsular serotypes, other virulence determinants have also been reported for K. pneumoniae liver abscesses, including the presence of hypermucoviscosity, aerobactin, magA (mucoviscosity-associated gene A), rmpA (regulator of mucoid phenotype), kfu (responsible for an iron uptake system) and allS (associated with allantoin metabolism) genes.…”
mentioning
confidence: 99%
“…[1][2][3][4] Its emergence in western countries has also been reported. [5][6][7] Previous studies in Taiwan, Singapore and Korea found a high prevalence of the capsular polysaccharide (CPS) K antigen serotypes K1 (54.5-63.4%) and K2 (5-21.2%) of K. pneumoniae in liver abscess isolates. 1,[8][9][10] Apart from the capsular serotypes, other virulence determinants have also been reported for K. pneumoniae liver abscesses, including the presence of hypermucoviscosity, aerobactin, magA (mucoviscosity-associated gene A), rmpA (regulator of mucoid phenotype), kfu (responsible for an iron uptake system) and allS (associated with allantoin metabolism) genes.…”
mentioning
confidence: 99%
“…Recent studies have shown that the mucoviscosity-associated gene A (magA) and regulator of mucoid phenotype A (rmpA) are associated with this syndrome [9,[12][13][14]17]. However, we could not ascertain which phenotype and genotype produced invasive K. pneumoniae syndrome in our case.…”
Section: Discussionmentioning
confidence: 67%
“…pneumoniae has been reported to be the most common pathogen causing liver abscess in Korea [6,7]. The incidence of K. pneumoniae infection increases in immunocompromised conditions, such as diabetes mellitus, alcoholism, malignancy, hepatobiliary disease, chronic obstructive pulmonary disease, glucocorticoid therapy and renal failure [6][7][8][9][10][11][12][13][14]. In our case, the In a few cases, K. pneumoniae liver abscess has been associated with metastatic infection at other sites [7,8,[10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…2 Clinicians in the United States are just becoming aware of this syndrome, even though several articles about the Taiwanese experience have appeared in English language journals. [6][7][8] More recently there have been case reports of Kp liver abscesses in Asians living in the United States and Europe, [9][10][11][12] and even cases in non-Asian who have never traveled to Asia, 13 indicating that the spread of virulent Kp to the United States has occurred. The US strains carry many of the virulence-associated genes that have been identified in Taiwan.…”
mentioning
confidence: 99%